A Igreja vai à guerra ou a guerra se torna o altar da Igreja? Primazia eclesiástica e violência na Inglaterra (1318-1328) - Azevedo, Janaina Bruning (2022)
This dissertation has as main objective to comprehend the relations between ecclesiastical power and violence in 14th century England in order to present the hypothesis that ecclesiastical involvement in matters such as war or in other dimensions of violence, made possible the inversion of Primacy of the Church to the Archbishopric of York. Therefore, two concepts form the basis of the construction of the hypothesis: battle and crisis. These, in turn, do not belong to a specific historiography, but they are shaped and defined from the very interpretations made from the sources used here. Thus, they become historically constructed concepts, since their “origin”, if we can say so, are built through ideas that are painted and subject to observations in two types of sources, in other words, from different typologies and narratives and that has been written in different times. To build them and to reach our hypothesis, we used documents of a jurisdictional nature, such as CALENDAR of Close Rolls, CALENDAR of Fine Rolls and CALENDAR of Patent Rolls. We selected nine volumes of jurisdictional that correspond to the years from 1318 to 1328. The second typology are the chronicles: The Chronicle of Lanercost (1272-1346), edition of 1913, by Sir Herbert Maxwell; Vita Edwardi Secundi: Life of Edward the Second, 2005 and bilingual edition, by Wendy R. Childs. In this way, the dissertation unfolds in historiographical discussions about the theme of this research, which are the reign of Edward II (1307-1327), the Scottish Wars of Independence, the supposed crises in 14th century England, and the reversal of Primacy of the Church to the Archbishopric of York in three different years: 1318, 1322 and 1328. Likewise, it is intended to highlight, throughout the chapters, how the problems listed by the historiography itself and by the questions made to the documentary corpus are solved.